Molecular and Cellular Mediators of the Gut-Liver Axis in the Progression of Liver Diseases - Bruneau, Alix; Hundertmark, Jana; Guillot, Adrien; Tacke, Frank (Frontiers in Medicine, 2021)
The gut-liver axis covers the bidirectional communication between the gut and the liver, and thus includes signals from liver-to-gut (e.g., bile acids, immunoglobulins) and from gut-to-liver (e.g., nutrients, microbiota-derived products, and recirculating bile acids). In a healthy individual, liver homeostasis is tightly controlled by the mostly tolerogenic liver resident macrophages, the Kupffer cells, capturing the gut-derived antigens from the blood circulation. However, disturbances of the gut-liver axis have been associated to the progression of varying chronic liver diseases, such as non-alcoholic fatty liver disease, non-alcoholic steatohepatitis, and primary sclerosing cholangitis. Notably, changes of the gut microbiome, or intestinal dysbiosis, combined with increased intestinal permeability, leads to the translocation of gut-derived bacteria or their metabolites into the portal vein. In the context of concomitant or subsequent liver inflammation, the liver is then infiltrated by responsive immune cells (e.g., monocytes, neutrophils, lymphoid, or dendritic cells), and microbiota-derived products may provoke or exacerbate innate immune responses, hence perpetuating liver inflammation and fibrosis, and potentiating the risks of developing cirrhosis. Similarly, food derived antigens, bile acids, danger-, and pathogen-associated molecular patterns are able to reshape the liver immune microenvironment. Immune cell intracellular signaling components, such as inflammasome activation, toll-like receptor or nucleotide-binding oligomerization domain-like receptors signaling, are potent targets of interest for the modulation of the immune response. This review describes the current understanding of the cellular landscape and molecular pathways involved in the gut-liver axis and implicated in chronic liver disease progression. We also provide an overview of innovative therapeutic approaches and current clinical trials aiming at targeting the gut-liver axis for the treatment of patients with chronic liver and/or intestinal diseases.